Визначення оптимальної тривалості збирання зернових - Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич; Ihnatiev, Yevhen (ТДАТУ, 2016)
The paper presents simple method for determining the optimal duration of grain harvesting, depending on the age and grade technique that allows to reduce crop losses during its harvesting.
Keywords: harvest duration; grain loss; technics age structure; harvest; technical condition of equipment; costs